Proyeksi Emisi Gas Rumah Kaca Sektor Energi Transportasi Kendaraan Dinas Universitas Mulawarman - Syarawie, Muhammad Mutawallie; Subagiada, Kadek; Natalisanto, Adrianus Inu (Progressive Physics Journal, 2024)
Research on projections of greenhouse gas emissions has been carried out in the sector of transportation energy for official vehicles in Mulawarman University. The study used secondary data of fuel use of the official vehicles from 2015 until 2019 to determine the greenhouse gas emissions dominated by CO2 , CH 4 dan N2 O. The trend of the obtained greenhous gas emissions was used to predict the greenhouse gas emissions in the range of 2020 and 2030. The projections of CO 2 emissions, CH 4 emissions, and N2 O emissions, in the years, respectively, are 427,281 tons of CO2 -eq, 5,697 tons of CO2 -eq, and 5,228 tons of CO2 -eq. The calculation revealed that in the next eleven years the projection of the greenhous gas emissions due to the use of official vehicle fuel in Mulawarman University will reduce continuously.